Education Media about Stunting Prevention on Adolescents in Islamic Boarding Schools - Dwi Ayu Marlinawati (Journal of Educational, Health and Community Psychology, 2023)
The provision of education about stunting prevention in adolescents needs to be carried out in line with the high prevalence of stunting under five in Indonesia today. This study aims to analyze the effect of providing education about stunting prevention on the Knowledge and attitudes of adolescents at Islamic boarding schools in Kendal Regency. This study used a quasi-experimental pre-post test with a control group design. The research media are animated videos and booklets. Respondents were adolescents at Islamic boarding schools who were divided into the intervention group (n=63) and the control group (n=63). Data analysis used independent sample t-test, multiple linear regression, and gain score. The results showed that there was an effect of providing education about stunting prevention through animated videos and booklets on the knowledge (p=0.000) and attitudes (p=0.000) of adolescents in Islamic boarding schools, as well as an increase in the average gain score of Knowledge (63.99%) and attitudes (58.49%). Providing education through animated videos and booklets can increase the Knowledge and attitudes of adolescents in Islamic boarding schools. Therefore, periodic and consistent education is needed to overcome stunting problems from an early age.